Chnoospora minima Polysaccharide-Mediated Green Synthesis of Silver Nanoparticles: Potent Anticancer and Antimicrobial Activities - Lakshika Keerthirathna; Sachini Sigera; Milan Rathnayake; Arunoda Senarathne; Hiruni Udeshika; Chamali Kodikara; Narayana M. Sirimuthu; Kalpa W. Samarakoon; Mohamad Boudjelal; Rizwan Ali; Dinithi C. Peiris (Biology)
Marine algae offer environmentally friendly platforms for green nanoparticle synthesis. This study reports the biosynthesis of silver nanoparticles using polysaccharides isolated from the brown alga Chnoospora minima (PAgNPs) and evaluates their therapeutic potential. Fourier Transform Infrared Spectroscopy (FTIR) confirmed algal polysaccharide functional groups. Dynamic Light Scattering (DLS), Scanning Electron Microscopy (SEM), and Energy Dispersive X-ray (EDX) analysis characterized the nanoparticles as spherical (~84 nm average size), stable (zeta potential −18.5 mV), and containing elemental silver without nitrogen. The PAgNPs exhibited potent antioxidant activity (~100% DPPH scavenging) and significant antimicrobial efficacy, particularly against Staphylococcus aureus and Candida species. Crucially, PAgNPs displayed potent antiproliferative activity against human lung cancer cells (A549, IC50: 13.59 µg/mL). In contrast, toxicity to normal Vero cells was significantly lower (IC50: 300.2 µg/mL), demonstrating notable cancer cell selectivity (SI 22.1). Moderate activity was observed against MCF-7 breast cancer cells (IC50: 100.7 µg/mL). These results demonstrate that C. minima polysaccharide facilitates the synthesis of biocompatible AgNPs with promising antimicrobial and selective anticancer capabilities, highlighting their potential for further development as nanotherapeutics.